Information system definition of adaptation opportunities of the students organism - Порван, Андрей Павлович; Журавлева, Юлия Владимировна (Technology audit and production reserves, 2013)
The creation of the information system of definition of adaptive capabilities of students is considered in the paper. The problems of studying the functional capabilities of an organism, features of adaptation of students and their psycho-emotional state are highlighted. The main objective of the study is the development of methods and systems for the collection, processing and analysis of the data, obtained using technical means, as well as the use of medical and psychological knowledge. The information analysis includes the integrated assessment of adaptation capabilities of the student’s body, which involves the research of the overall variability by the spectral and temporal method, the dynamic component of the heart rate variability; the definition of the level of depression and anxiety and the estimation of distribution and switching of attention on the corresponding psychological tests. The proposed system allows to obtain the qualitative assessment of the adaptation capabilities of the student’s body taking into account the functional class and psycho-emotional state.